Evaluasi Program Peningkatan Kompetensi Hakim Melalui Pelatihan yang Terintegrasi dan Berkelanjutan di Indonesia - Indriati Amarini (Fakultas Hukum Universitas Islam Indonesia, 2018)
The ability of judges to make decisions is acquired from their experiences during the career that they have undergone. The problems formulated in this study were, first why is it necessary to improve the competence of judges through trainings of judges? Second, how is the model of judge competence improvement program aimed to create professional and authoritative judges with high integrity? This was a socio-legal or non-doctrinal research. The results of this study indicated that: first, judge training programs are highly necessary in order to create professional and authoritative judges with high integrity. Besides, these trainings also serve as a means to improve the quality of judge decisions and judge competencies, including professional competence, personal competence, social competence, and leadership competence. Second, the model of judge competence improvement program to create professional and authoritative judges with high integrity is through integrated and continuous trainings.